Nourishing Kenya’s youth: A spatial analysis of demographic change and food demand - Waithera, Regina; Song, Chun; Yego, Francis (2025)
• Nutrition during adolescence is critical for human capital formation • Ensuring adequate nutritional support for young populations remains a key policy challenge in Kenya, particularly in regions with large youth populations. • Spatial analysis reveals that certain counties in Kenya may face greater challenges in nourishing their young populations in the future • Integrating spatial explicit modelling results on food demand with demographic trends are key for ensuring nutrition security for the youth.